Predictive factors for positive diagnosis of malignant biliary strictures by transpapillary brush cytology and forceps biopsy. Issue 1 (January 2016) - Naitoh, Itaru; Nakazawa, Takahiro; Kato, Akihisa; Hayashi, Kazuki; Miyabe, Katsuyuki; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Yoshida, Michihiro; Umemura, Shuichiro; Hori, Yasuki; Kuno, Toshiya; et al.
Abstract : Objective: The diagnostic yields of endoscopic transpapillary brush cytology and forceps biopsies for malignant biliary strictures (MBS) remain unclear and predictive factors for diagnosis have not been established. We aimed to clarify the diagnostic yields of both methods and the predictive factors Methods: We reviewed 241 patients with biliary strictures who underwent transpapillary brush cytology ( n  = 202) or forceps biopsy ( n  = 208) between 2004 and 2014 at a single academic center. Results: The sensitivity of forceps biopsy for MBS was significantly higher than that of brush cytology [60.6% (97/160) vs 36.1% (57/158), P  < 0.01). The sensitivity of forceps biopsy was significantly higher in diagnosing bile duct cancer than pancreatic cancer [78.8% (52/66) vs 42.4% (28/66), P  < 0.01). Multivariate analysis revealed that serum total bilirubin (TB) level (T‐Bil) ≥ 4 mg/dL [odds ratio (OR) 2.506, 95% confidence interval (CI): 1.139–5.495, P  = 0.022) was an independent predictor for positive diagnosis by brush cytology, while bile duct cancer (OR 4.926, 95% CI 2.183–11.111, P  < 0.001), stricture length ≥ 30 mm (OR 2.941, 95% CI 1.119–7.752, P  = 0.029) and TB ≥4 mg/dL (OR 2.252, 95% CI 1.052–4.831, P  = 0.037) were significant indicators of a positive diagnosis by forceps biopsy. Conclusions: Endoscopic transpapillary forceps biopsy shows higher sensitivity than that of brush cytology for MBS. Bile duct cancer, stricture length ≥ 30 mm and TB ≥4 mg/dL are good indicators of forceps biopsy.